Design and implementation of mobile video service quality analysis system - Gang ZHAO (Dianxin kexue)
Customer perception of mobile video service not only depends on the quality of the network,but also depends on the role of “end,pipeline,cloud,platform”.It is urgent to change the quality assurance mechanism based on the network itself to the end-to-end horizontal integration of customer perception.To solve these problems,the design and implementation of a mobile video service quality analysis system was introduced.The analysis model was established from service,flow direction,area,network element,community and terminal in order to analyze the data source in each part of the mobile video service; key KQI and changing trend of video services was presented,constant performance monitoring was carried out; the problem was found from the users’ perspective,trend analysis of performance deterioration,cause analysis of performance deterioration; automatic or manual processing of the identified problems by distribution work order was carried out,the problems were solved by antomatically or manual dispatch,closed-loop management mechanism was established.This system could improve the management level of mobile video service quality and reduce the cost notably significantly.The framework of the system and the realization of main function part was introduced in detail,and examples of system applications were described.